Differential effects of ocean acidification on carbon acquisition in two bloom‐forming dinoflagellate species. Issue 4 (24th January 2014) - Eberlein, Tim; Van de Waal, Dedmer B.; Rost, Björn
<x xml:space="preserve">Abstract</x> Dinoflagellates represent a cosmopolitan group of phytoplankton with the ability to form harmful algal blooms. Featuring a Ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (RubisCO) with very low CO2 affinities, photosynthesis of this group may be particularly prone to carbon limitation and thus benefit from rising atmospheric CO2 partial pressure (pCO2) under ocean acidification (OA). Here, we investigated the consequences of OA on two bloom‐forming dinoflagellate species, the calcareous Scrippsiella trochoidea and the toxic Alexandrium tamarense. Using dilute batch incubations, we assessed growth characteristics over a range of pCO2 (i.e. 180–1200 µatm). To understand the underlying physiology, several aspects of inorganic carbon acquisition were investigated by membrane‐inlet mass spectrometry. Our results show that both species kept growth rates constant over the tested pCO2 range, but we observed a number of species‐specific responses. For instance, biomass production and cell size decreased in S. trochoidea, while A. tamarense was not responsive to OA in these measures. In terms of oxygen fluxes, rates of photosynthesis and respiration remained unaltered in S. trochoidea whereas respiration increased in A. tamarense under OA. Both species featured efficient carbon concentrating mechanisms (CCMs) with a CO2‐dependent contribution of HCO3− uptake. In S. trochoidea, the CCM was further facilitated by exceptionally high and CO2‐independent carbonic anhydrase activity. Comparing both species, a general trade‐off between maximum rates of photosynthesis and respective affinities is indicated. In conclusion, our results demonstrate effective CCMs in both species, yet very different strategies to adjust their carbon acquisition. This regulation in CCMs enables both species to maintain growth over a wide range of ecologically relevant pCO2.